THE IMPACT OF MONITORING MECHANISMS ON THE FORMATION OF FINANCIAL STABILITY INDICATORS IN BANKS (Лучшие интеллектуальные исследования, 2025)
Abstract: This article analyzes the role and practical impact of monitoring mechanisms in shaping financial stability indicators in the banking sector. Financial stability is considered a key factor that ensures the uninterrupted, secure, and competitive operation of banks. Monitoring mechanisms contribute to strengthening stability by systematically assessing bank performance, identifying risk factors, and tracking the dynamics of financial indicators. The article examines how key stability indicators—liquidity level, capital adequacy, profitability ratios, and credit portfolio quality—are formed through monitoring tools.Аннотация: В данной статье рассматривается роль и практическое значение механизмов мониторинга в формировании показателей финансовой устойчивости в банковской системе. Финансовая устойчивость рассматривается как ключевой фактор, обеспечивающий непрерывную, безопасную и конкурентоспособную деятельность банков. Механизмы мониторинга способствуют укреплению устойчивости банков за счёт систематической оценки их деятельности, выявления рисков и отслеживания динамики финансовых показателей. В статье анализируется формирование основных показателей устойчивости — уровня ликвидности, достаточности капитала, показателей рентабельности и качества кредитного портфеля — с использованием инструментов мониторинга.